Study of Treatment in Heart Disease Patients Installation in Undata Hospital, Central Sulawesi - Niluh Puspita Dewi; Indah Kurnia Utami; Al'vira Gunawan; Muh. Thamrin Tahir; Syafika Alaydrus; Nani Astria Polontalo (Journal of Public Health and Pharmacy)
Introduction: Heart diseasesis a disorder of heart functionsdue to lack of bloods in the heart muscles due to narrowingsof the coronary artery. The purposesof this study was to describe t he characteristics and use of heart disease drugs based on parameters of rationality of drug use in Undata Hospital, Central Sulawesi Province including gender, age, heart drug class, complementary drug class, length of hospitalization, laboratory data, comorbidities , appropriate indications, the right drugs and the right dose.